Highly sensitive, label-free detection of 2,4-dichlorophenoxyacetic acid using an optofluidic chip - Feng, Xueling (2020)
A highly sensitive approach for rapid and label-free detection of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) using an optofluidic chip is demonstrated. The optofluidic chip is prepared by covalent immobilization of 2,4-D-bovine serum albumin (2,4-D-BSA) conjugate to an integrated microring resonator. Subsequent detection of 2,4-D carried out in a competitive immunoreaction format enables selective detection of 2,4-D in different types of water samples, including bottled, tap, and lake water, at a limit of detection (LOD) of 4.5 pg/mL and in a quantitative range of 15-105 pg/mL. The microring resonator-based optofluidic chip is reusable with ultrahigh sensitivity that offers real-time and on-site detection of low-molecular-weight targets for potential applications in food safety and environmental monitoring.